Regulate and be regulated: integration of defense and other signals by the AtMYB30 transcription factor - Raffaele, Sylvain; Rivas, Susana (Frontiers in Plant Science, 2013)
Transcriptional regulation in host cells plays a crucial role in the establishment of plant defence and associated cell death in response to pathogen attack. Here, we review our current knowledge of the transcriptional control of plant defences with a focus on the MYB family of transcription factors. Within this family, the Arabidopsis MYB protein AtMYB30 is a key regulator of plant defences and one of the best characterized MYB regulators directing defence-related transcriptional responses. The crucial role played by AtMYB30 in the regulation of plant disease resistance is underlined by the finding that AtMYB30 is targeted by the Xanthomonas type III effector XopD resulting in suppression of AtMYB30-mediated plant defences. Moreover, the function of AtMYB30 is also tightly controlled by plant cells through protein-protein interactions and post-translational modifications. AtMYB30 studies highlight the importance of cellular dynamics for defence-associated gene regulation in plants. Finally, we discuss how AtMYB30 and other MYB transcription factors mediate the interplay between disease resistance and other stress responses.